Examining the Impact of Structural Racism on Food Insecurity: Implications for Addressing Racial/Ethnic Disparities. (April 2018) - Odoms-Young, Angela; Bruce, Marino A.
Abstract : Food insecurity is defined as "a household-level economic and social condition of limited or uncertain access to adequate food." While, levels of food insecurity in the United States have fluctuated over the past 20 years; disparities in food insecurity rates between people of color and whites have continued to persist. There is growing recognition that discrimination and structural racism are key contributors to disparities in health behaviors and outcomes. Although several promising practices to reduce food insecurity have emerged, approaches that address structural racism and discrimination may have important implications for alleviating racial/ethnic disparities in food insecurity and promoting health equity overall.